Habitat Segregation among Trophic Morphs of the Cuatro Ciénegas Cichlid (Herichthys minckleyi - Cohen, Adam E.; Hendrickson, Dean A.; Parmesan, Camille; Marks, Jane C. (HIDROBIOLÓGICA, 2017)
Herichthys minckleyi is an endangered, trophically polymorphic cichlid endemic to the Cuatro Ciénegas basin of Coahuila, Mexico. A molariform morph has stout pharyngeal teeth whereas a papilliform morph has numerous fine pharyngeal teeth. Individuals with intermediate pharyngeal dentition also exist, as does yet another morph, called piscivore. Previous studies indicated that morphs utilize different food sources, thus suggesting morph-specific spatial segregation, since food resource availability is spatially heterogeneous. We present data from an observational study of all morphs (but focusing on the three most common, normal-bodied ones molariform, papilliform and intermediate) in a single spring pool, Poza Mojarral Oeste. We analyzed morph distribution in relation to habitat types, and document morph-specific differences in feeding behavior. Spatio-temporal habitat partitioning was also investigated. Habitat use by molariform, papilliform, and intermediate morphs was found to be non-random. Morphs differed in habitat use, albeit with considerable overlap. Strong segregation among morphs was not detected in any season or time of day, but habitat use patterns varied seasonally within each morph and were consistently different among morphs. All morphs behave basically as feeding generalists. This endangered species may prove more difficult to manage than other, non-polymorphic species. It is clearly important to manage not only for the maintenance of the species, but also for maintenance of its different morphs, which our study indicates may each require different mixes of habitat types. We thus hypothesize that any changes in habitat heterogeneity will lead to altered proportions of the different morphs of the species.